Respuesta :
Answer:
8x - 5y - 13
Step-by-step explanation:
(6x - 3y - 12) - (2x +2y - 10)
(6x - 3y - 12) - 2x - 2y + 10
6x - 3y - 23 - 2x - 2y + 10
8x - 5y - 13
Answer:
4x+y=22
Step-by-step explanation:
6x+3y-12-(2x+2y)=10
Based on BODMAS we will have to deal with the bracket first
6x+3y-12-2x-2y=10
To continue with the solution we will have to collect like terms
That is,
6x-2x+3y-2y=10+12
4x+y=22
This can't be solved further because we don't really know the value of x and y...it can only be solved further by knowing the value of either x or y but we are not given...so we will have to leave our final answer to be
4x+y=22